A Commentary to Kant’s ‘Critique of Pure Reason’ - Smith, Norman Kemp. author. aut Link
LXIV, 651 p.
Keywords: Of all the major philosophical works, Kant's Critique of Pure Reason is one of the most rewarding, yet one of the most difficult. Norman Kemp Smith's Commentary elucidates not only textural questions and minor issues, but also the central problems which arise, he contends, from the conflicting tendencies of Kant's own thinking. Kemp Smith's Commentary continues to be in demand with Kant Scholars, and it is being reissued here with a new introduction by Sebastian Gardner to set it in its contemporary context.